Відповідальність за невиконання (неналежне виконання) договору про надання юридичних послуг: окремі питання - Жорнокуй, Ю. М.; Zhornokui, Yu. M.; Жорнокуй Юрій Михайлович (Наше право. - 2023. - № 1. - С. 115-123, 2023)
Проведено аналіз законодавства, доктринальних підходів та судової практики в України щодо розуміння проблемних питань притягнення до відповідальності за невиконання (неналежне виконання) договору про надання юридичних послуг. Наголошено, що: 1) розділ про відповідальність сторін за цим договором, як самостійний, має міститися у кожному такому договорі, що зумовлено специфікою надання цих послуг; 2) на сьогодні відсутній єдиний підхід до визначення критеріїв оцінки якості юридичних послуг, що не сприяє відповіді на питання про їх якість та встановлення критеріїв їх оцінки.

The author of the article has analyzed the legislation of Ukraine, as well as doctrinal approaches and caselaw to understanding the problematic issues of bringing to responsibility for non-performance (improper performance) of legal services supply agreement. It has been concluded that the lack of responsibility conditions in a specifi c agreement implies the application of general rules on responsibility for breaking contractual obligations. We believe that the section on the responsibility of the parties under legal services supply agreement must be in every specifi c contract as an independent one, since the general provisions of the Civil Code of Ukraine regarding responsibility for non-performance (improper performance) of obligations, including under general provisions on services supply agreement, do not fully correspond to the specifi cs of legal services supply agreement, which is determined by the nature of the very service, professional knowledge and skills of the person who provides it, as well as not always by the guaranteed result of the provided service expected by the customer. At the same time, responsibility of the parties under legal services supply agreement should be one of its mandatory and essential conditions. It has been emphasized that the legislation and legal doctrine of Ukraine do not contain a single approach to determining the criteria for assessing the quality of both legal services directly and services as the object of civil rights in general. The specifi cs of the legal service do not allow to formulate defi nite requirements for the activity of its performer in the very contract, which makes it much more diffi cult to resolve the issue of the possibility of bringing the performer to responsibility in case of improper performance of the obligation. The above does not contribute to a clear answer to the question on the quality of legal services and the establishment of general, the most important and necessary criteria for its evaluation.

Проведен анализ законодательства, доктринальных подходов и судебной практики Украины относительно понимания проблемных вопросов привлечения к ответственности за невыполнение (ненадлежащее исполнение) договора о предоставлении юридических услуг. Отмечено, что: 1) раздел об ответственности сторон по настоящему договору как самостоятельный должен содержаться в каждом таком договоре, что обусловлено спецификой предоставления этих услуг; 2) на сегодняшний день отсутствует единый подход к определению критериев оценки качества юридических услуг, что не способствует ответу на вопрос об их качестве и установлении критериев их оценки.
Responsibility for nonperformance (improper performance) of legal services supply agreement: some aspects
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; договір про надання юридичних послуг; contract of provision legal services; договор о предоставлении юридических услуг; цивільно-правова відповідальність; civil liability; гражданско-правовая ответственность; відповідальність за невиконання зобов’язань; liability for non-fulfillment of obligations; ответственность за невыполнение обязательств; неналежне виконання договору; improper performance of the contract; ненадлежащее исполнение договора